Koper: portable surgery clinic / Rizqiawan Surya Mahendra ... [et al.] - Mahendra, Rizqiawan Surya; Nugroho, Hanung Cahyo Adi; Faizahaq, Raden Rara Lulu; Abdurrahman, Hilman (2020)
Indonesia is one of the countries that has high intensity and potential for natural disasters such as earthquakes and tsunamis moreover Indonesia is surrounded by the Ring of Fire. These natural disasters often result in damage to buildings and health facilities. Meanwhile health facilities are urgently needed when a disaster occurs. The difficulty in mobility from the evacuation area to health facility is also an obstacle. In addition, natural disasters results in many victims experiencing fractures and bleeding. The existing facility has constraints in dimensions, materials, inefficient fabrication time and a difficulty in distributing the facility to the disaster area in a limited time. By using the Glass Box design method and approaches to the easy-mobility, sterilisation and standard health facility thereby KOPER is created. The purpose of this facility is to create a post-disaster health facility that has standard surgery health function to accommodate disaster emergency in particular bleeding and fractures cases and easy mobility from and to the disaster evacuation area. Therby there is the design of KOPER or Portable Surgery Clinic that carries effectiveness, efficiency and compactness and is equipped with lightweight materials, folding techniques, standard surgery equipment with sterilization space facility inside the Portable Clinic design.